Bayesian Information and the Precautionary Demand for Money - Stanhouse, Bryan E. (Journal of Political Economy, 1982)
In this paper, I demonstrate how Bayesian information may be analyzed as a bona fide input in determining the optimal level of precautionary balances to hold. I first examine the impact of information in revising the expected total cost function and the effect of information on optimal precautionary cash balances. I then derive the optimal demand for information, and the comparative statics of θ * are developed. Finally, I examine the elasticity of precautionary balances to scale under the assumption that the degree of uncertainty of cash needs is a decision variable for the firm or household to determine. Surprisingly, monetary balances demonstrate significant economies of scale with endogenous information.